2016
DOI: 10.1111/1751-2980.12398
|View full text |Cite
|
Sign up to set email alerts
|

Vonoprazanversusconventional proton pump inhibitor‐based triple therapy as first‐line treatment againstHelicobacter pylori: A multicenter retrospective study in clinical practice

Abstract: Vonoprazan-based triple therapy is feasible, and has a higher rate for H. pylori eradication than conventional PPI as a first-line regimen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 40 publications
0
17
1
Order By: Relevance
“…In recent years, several studies have compared eradication rates between VPZ-containing and PPI-containing triple therapies across centers in Japan. As shown in Table 2, up until September 2018, 23 reports had investigated the efficacy of first-line VPZ-containing therapy (21 reports for VPZ/AMX/CLR and 2 reports for VPZ/MNZ/CLR) (Matsumoto et al, 2016; Murakami et al, 2016; Noda et al, 2016; Shichijo et al, 2016; Shinozaki et al, 2016, 2018; Suzuki et al, 2016; Tsujimae et al, 2016; Yamada et al, 2016; Kajihara et al, 2017; Katayama et al, 2017; Maruyama et al, 2017; Nishizawa et al, 2017; Ono et al, 2017; Sakurai et al, 2017; Sue et al, 2017a,b, 2018a; Sugimoto et al, 2017; Tanabe et al, 2017, 2018; Mori et al, 2018; Ozaki et al, 2018), and 19 reports had compared the efficacy between VPZ-containing therapy and PPI-containing therapy, including 3 randomized control trials (Murakami et al, 2016; Maruyama et al, 2017; Sue et al, 2018a) and 16 non-randomized retrospective cohort trials (Matsumoto et al, 2016; Noda et al, 2016; Shichijo et al, 2016; Shinozaki et al, 2016; Suzuki et al, 2016; Tsujimae et al, 2016; Yamada et al, 2016; Kajihara et al, 2017; Nishizawa et al, 2017; Ono et al, 2017; Sakurai et al, 2017; Sue et al, 2017a,b; Mori et al, 2018; Ozaki et al, 2018; Tanabe et al, 2018).…”
Section: First-line Vonoprazan-containing Eradication Therapymentioning
confidence: 99%
“…In recent years, several studies have compared eradication rates between VPZ-containing and PPI-containing triple therapies across centers in Japan. As shown in Table 2, up until September 2018, 23 reports had investigated the efficacy of first-line VPZ-containing therapy (21 reports for VPZ/AMX/CLR and 2 reports for VPZ/MNZ/CLR) (Matsumoto et al, 2016; Murakami et al, 2016; Noda et al, 2016; Shichijo et al, 2016; Shinozaki et al, 2016, 2018; Suzuki et al, 2016; Tsujimae et al, 2016; Yamada et al, 2016; Kajihara et al, 2017; Katayama et al, 2017; Maruyama et al, 2017; Nishizawa et al, 2017; Ono et al, 2017; Sakurai et al, 2017; Sue et al, 2017a,b, 2018a; Sugimoto et al, 2017; Tanabe et al, 2017, 2018; Mori et al, 2018; Ozaki et al, 2018), and 19 reports had compared the efficacy between VPZ-containing therapy and PPI-containing therapy, including 3 randomized control trials (Murakami et al, 2016; Maruyama et al, 2017; Sue et al, 2018a) and 16 non-randomized retrospective cohort trials (Matsumoto et al, 2016; Noda et al, 2016; Shichijo et al, 2016; Shinozaki et al, 2016; Suzuki et al, 2016; Tsujimae et al, 2016; Yamada et al, 2016; Kajihara et al, 2017; Nishizawa et al, 2017; Ono et al, 2017; Sakurai et al, 2017; Sue et al, 2017a,b; Mori et al, 2018; Ozaki et al, 2018; Tanabe et al, 2018).…”
Section: First-line Vonoprazan-containing Eradication Therapymentioning
confidence: 99%
“…In 2016, a phase III randomized, double-blind study reported an eradication rate of 92.6% (95% CI: 89.2–95.2%) using a first-line vonoprazan-containing regimen and 75.9% (70.9–80.5%) using a lansoprazole-containing regimen [ 12 ]. Other studies have reported that the efficacy of first-line vonoprazan-containing regimens ranges from 82.9% to 94.6% [ 13 , 14 , 15 , 16 , 29 , 30 , 31 ]. Based on 21 studies that investigated a total of 12,010 patients receiving PPI-containing first-line therapy, no studies reported an eradication rate higher than 85% [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study reported that vonoprazan 20 mg inhibits H + /K + -ATPase activity at a 400-fold lower dose than lansoprazole 30 mg at pH 6.6 [ 11 ]. Therefore, vonoprazan-containing eradication therapy appears to have a higher eradication rate than PPI-containing regimen [ 12 , 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Vonoprazan 20 mg demonstrated a more rapid and sustained acid-inhibitory effect than esomeprazole 20 mg or rabeprazole 10 mg [69]. Recent studies revealed that P-CAB based triple therapy was more effective than PPI-based triple therapy as a first-line H. pylori eradication method [7073]. Furthermore, even in the presence of clarithromycin-resistant strains, P-CAB-based triple therapy showed good eradication rates that were superior to those for PPI-based triple therapy (76.1% versus 40.2%) [74].…”
Section: First-line Treatment Options For Cases With High Antibiotmentioning
confidence: 99%